Capture the flag - Messner, Kate (Scholastic Press, 2012)
When the original Star Spangled Banner is stolen, seventh-graders Anne, José, and Henry, all descendants of the Silver Jaguar Society, pursue suspects on airport carts and through baggage handling tunnels while stranded at a Washington, D.C., airport during a snowstorm.